Ibadurrahman Character Profiles as a Role Model for Gen Z: A Comparative Analysis of Tafsir Al-Munir and Al-Misbah (QS. Al-Furqan: 63-77): Profil Karakter Ibadurrahman Sebagai Role Model Generasi Z: Studi Analisis-Komparatif Tafsir al-Munir dan Tafsir al-Misbah dalam QS. Al-Furqan Ayat 63–77 - Sulistyowati, Octalia Heri; Imawan, Dzulkifli Hadi (ABHATS: Jurnal Islam Ulil Albab, 2026)
Generation Z currently faces a complex digital paradox, where unlimited access to information is accompanied by identity crises, anxiety, and the attitude–behavior gap phenomenon, a discrepancy between value awareness and actual behavior. This study aims to reconstruct the character profile of ‘Ibād al-Raḥmān found in QS. Al-Furqan verses 63–77 as an alternative role model and curative solution to these problems. This study employs a qualitative method (library research) using thematic (mawḍū‘ī) and comparative (muqāran) exegesis approaches. The primary data sources are Tafsir al-Munir by Wahbah al-Zuḥaylī and Tafsir al-Misbah by M. Quraish Shihab. The results indicate a complementary synergy between the two scholars: al-Zuḥaylī emphasizes normative-theological aspects (legal obedience and eschatological orientation), while Quraish Shihab highlights sociological-humanist aspects (social stability and psychological well-being). The synthesis of these interpretations produces four main character dimensions: social ethics, spiritual balance, personal integrity, and transcendental awareness. Through recontextualization, the character of ‘Ibād al-Raḥmān proves relevant in addressing Generation Z’s challenges: the attribute of haunan (humility) serves as an antithesis to the culture of showing off (flexing), anti-zūr integrity functions as digital literacy ethics against hoaxes, and the practice of qiyām al-layl acts as a healing mechanism for mental health. [Generasi Z saat ini menghadapi paradoks digital yang kompleks, di mana kemudahan akses informasi justru diiringi dengan krisis identitas, kecemasan (anxiety), dan fenomena attitude–behavior gap atau kesenjangan antara kesadaran nilai dan perilaku nyata. Penelitian ini bertujuan untuk merekonstruksi profil karakter ‘Ibād al-Raḥmān yang termaktub dalam QS. Al-Furqan ayat 63–77 sebagai role model alternatif dan solusi kuratif bagi problematika tersebut. Penelitian ini menggunakan metode kualitatif (library research) dengan pendekatan tafsir tematik (mawḍū‘ī) dan komparatif (muqāran). Sumber data utama adalah Tafsir al-Munir karya Wahbah al-Zuḥaylī dan Tafsir al-Misbah karya M. Quraish Shihab. Hasil penelitian menunjukkan adanya sinergi komplementer antara kedua mufasir: al-Zuḥaylī menekankan aspek normatif-teologis (kepatuhan hukum dan orientasi akhirat), sedangkan Quraish Shihab menekankan aspek sosiologis-humanis (stabilitas sosial dan kesejahteraan psikologis). Sintesis kedua tafsir ini menghasilkan empat dimensi karakter utama, yaitu etika sosial, keseimbangan spiritual, integritas diri, dan kesadaran transendental. Melalui rekontekstualisasi, karakter ‘Ibād al-Raḥmān terbukti relevan untuk mengatasi tantangan Generasi Z: sifat haunan (rendah hati) sebagai antitesis budaya pamer (flexing), integritas anti-zūr sebagai etika literasi digital dalam melawan hoaks, serta praktik qiyām al-layl sebagai mekanisme healing bagi kesehatan mental.]